(Invited) Generation-Recombination Noise in Advanced CMOS Devices. (19th August 2016) - Simoen, Eddy; Oliveira, Alberto Vinícius de; Boudier, Dimitri; Mitard, Jerome; Witters, Liesbeth; Veloso, Anabela; Agopian, Paula Ghedini Der; Martino, Joao Antonio; Carin, Regis; Cretu, Bogdan; Langer, Robert; Collaert, Nadine; et al.
Abstract : This paper gives an overview of the occurrence of Generation-Recombination (GR) noise in advanced submicron Metal-Oxide-Semiconductor Field-Effect Transistors (MOSFETs). GR noise corresponds with a Lorentzian spectrum, characterized by a plateau amplitude and a corner frequency. Studying the gate voltage dependence of these parameters enables to distinguish trap centers in the depletion region of the semiconductor or in the gate dielectric. In the latter case, single defects are at the origin of the Lorentzian spectrum, which usually give rise to two-level fluctuations in the time domain, also called Random Telegraph Signals (RTSs). Here, it will be outlined how information regarding the energy level (ET ), the trap concentration (NT ) or the trap position can be extracted from studying the GR noise as a function of temperature or gate voltage.